Exploring the effects of CCTV upon fear of crime: A multi-level approach in Seoul. (June 2017) - Cho, Joon Tag; Park, Jisun
Abstract: We examined the effects of CCTV upon fear of crime through a multi-level analysis, using the Seoul Survey. We examined factors such as the number of CCTV cameras, crime rates, and disorder according to community and resident demographics. The results showed that the number of CCTV cameras was negatively associated with the fear of crime, but no significant effect was observed on the perceived risk of crime. In addition, the effects of CCTV differed by gender. The number of CCTV cameras was found to affect men's fear of crime but not women's fear of crime. Crime rates and disorder as regional-level factors were found to increase both fear of crime and the perceived risk of crime. The current findings emphasize the importance of scientific and systematic installation of CCTV cameras, active responses from police and related organizations to reduce crime and disorder, and the establishment of additional security measures for females.